“Oh my God I am alone”: young adult students’ experiences of living alone in a time of global uncertainty - Jenny M. Groarke; Lydia McKeown; Phoebe E. McKenna-Plumley; Lisa Graham-Wisener (International Journal of Adolescence and Youth)
This study explores young adult students’ experiences of living alone during the COVID-19 pandemic, addressing a vital research gap by investigating the collective influence of youth, student status, and solitary living on mental health. Remote semi-structured interviews were conducted with 18–24-year-olds in UK universities who had lived alone for at least 2 weeks between September 2020 and March 2021 (N = 8; 4 males; 19–24 years, M = 21.75). Reflexive thematic analysis identified four themes and two subthemes. Living alone was experienced as confinement, accompanied by loneliness and perceptions of loss and injustice. The experience significantly impacted mental health, which was exacerbated by social isolation and withdrawal. Accessing social support and connection through technology was protective. Findings have implications for the design of interventions for young people dealing with isolation. Improving emotion regulation and social skills and preventing social withdrawal are important intervention targets.